Potato glycoalkaloids detection based on conductometric sensor coupled to butyryl cholinesterase - Nazarenko, E.A.; Soldatkin, A.P.; Martelet, C.; Korpan, Ya.I. (Біополімери і клітина, 2004)
For the construction of a biosensor sensitive to some steroidal glycoalkaloids a conductometric planar electrode as a transducer and the horse serum butyryl cholinesterase (BuChE) as a biorecognition element have been used. It has been shown that α-solanine, α-chaconine and solanidine can be detected within the range of their concentrations from 0.2 to 100 mM depending on the type of steroidal alkaloid used. The detection limits were estimated to be 0.2 mM for chaconine and 0.5 mM for solanine/solanidine. The responses of the sensors developed were reproducible: the relative standard deviation was about 1.5 % and 5 % for intra- and inter-sensor responses, respectively. Moreover, one sensor with the immobilized enzyme can be used repeatedly (for at least 100 measurements) after a simple washing by buffer and can be stored at room temperature without substantial loss in activity of the immobilized enzyme not less than 1 month. It has been shown that all the analytes investigated inhibit reversibly and competitively the horse BuChE immobilized on the transducer surface. In assays, which combined α-solanine and α-chaconine, inhibition of BuChE was not additive. A possibility to apply the biosensor developed for the quantitative detection of the total steroidal alkaloids pool in foodstuffs and some biological samples is discussed.